Educational Leadership Models in Supporting Organizational Change Management in the Rice Milling Industry - setyobudi, agus; Hartono, Sri (PT. Technology Laboratories Indonesia (TechnoLabs), 2025)
Organizational change has become an unavoidable necessity for the rice milling industry as it responds to technological advancement, market competition, and increasing demands for efficiency and quality. In this context, leadership that emphasizes learning, capacity building, and adaptive behavior plays a strategic role in guiding organizational transformation. This study aims to examine educational leadership models and their contribution to supporting effective change management within the rice milling industry. The research adopts a qualitative descriptive approach through case studies involving rice milling enterprises undergoing organizational change. Data were collected through in-depth interviews, direct observation, and document analysis, and were analyzed using thematic analysis to identify leadership practices, change strategies, and their impacts on organizational performance. The findings indicate that educational leadership characterized by participatory decision-making, continuous learning, and empowerment of human resources significantly facilitates the change management process. Leaders who function as educators are able to enhance employee readiness, reduce resistance to change, and foster a culture of innovation and collaboration. This study concludes that the integration of educational leadership principles into organizational change management contributes to sustainable organizational development in the rice milling industry. The results are expected to provide theoretical contributions to leadership and change management studies, as well as practical implications for industry leaders facing similar transformation challenges.